Sistematika Tinjauan Literature Mengenai Overall Equipment Effectiveness (OEE) pada Industri Manufaktur dan Jasa - Welly Atikno; Humiras Hardi Purba (Program Studi Teknik Industri, Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2021)
Overall equipment effectiveness (OEE) is one of the performance evaluation methods used to measure the productivity of industrial equipment as a key performance indicator. Literature studies are used to identify, categorize, and synthesize research related to the application, study and analysis of OEE in various industries. This research is descriptive and the research method used is to conduct a systematic, structured and targeted review of 35 journals in Asia over the past eight years, with the scope of oee core characteristics and synergize the strength of the improvement framework, then group into manufacturing and service sectors. The results of this study explain that there are fundamental differences in the implementation of OEE in the manufacturing industry with services that are tangible manufacturing products, defects are determined through visual observation of the physical condition of products with certain criteria, the application of OEE affects the products produced. While in the service industry, the products produced are intangible, defects in the form of known data after going through the process of data processing using statistics with certain criteria, the application of OEE affects the services provided. Based on the results of this study is expected to provide systematic guidance to users overall equipment effectiveness (OEE) method in carrying out improvements to identify future development areas and as a reference in conducting further research in the field of manufacturing, services and in various other fields.